Teacher education policies, practices, and reform in Scotland: Implications in the Indian context - Pradeep Kumar Misra (Cogent Education, 2015)
India, a country of 1.27 billion, nowadays needs reforms, improvements, and new approaches in teacher education to cater to the demands of changing economy and society. This call to improve teacher education becomes more significant considering the fact that 50% of India’s current population is below the age of 25 and over 65% below 35. There are two ways to proceed in this direction. First, making an internal review and assessment of present scenario of teacher education and suggesting need-based measures. The second one is to learn from those countries that have recently reviewed their teacher education systems and are continuously working for the betterment of teacher education. Following second approach, present paper analyzes teacher education policies, practices, and reform in Scotland, argues that concerns and commitments to reform teacher education in India and Scotland are similar, and suggests implications of Scottish experiences in the Indian context.